Progressive interatrial block associated with atrial fibrillation in a patient with hypertrophic cardiomyopathy. Issue 3 (11th September 2016) - Britton, Samantha; Barbosa‐Barros, Raimundo; Alexander, Bryce; Baranchuk, Adrian
Abstract : Progressive interatrial block is a clinically significant condition that has previously been reported in various patient populations. It is a manifestation of progressive fibrosis affecting the Bachmann region. This report presents a case of progressive interatrial block associated with atrial fibrillation in the context of hypertrophic cardiomyopathy.